Yellow-nail syndrome: report of three cases. - Nakielna, E. M. (1976)
The yellow nail syndrome, a combination of yellow discolouration of and dystrophic changes in the nails, pleural effusions and lymphedema, is thought to be relatively rare; to date 44 cases have been reported. Of a further three patients with this syndrome, one had all three features, one had the yellow nails alone and the other had pleural effusions and lymphedema without classic nail changes. Each had recurrent lower respiratory tract infections; and of all 47, chronic pulmonary infections occurred in approximately one quarter and were frequently associated with chronic sinus infections. The underlying abnormality is presumed to be a congenital defect of the lymphatics, but so far this has not been demonstrated to be the cause of the nail changes, the pathogenesis of which remains obscure.